Early Mobilization Affected the Daily Living Activity based on Dependence on Post Patient Section Caesarian Operation - Arie Jefry Kaarayeno; Rachmat Chusnul Choeron (STIKes Patria Husada Blitar, 2023)
Early mobilization is a therapy for the ability of individuals to move freely, easily, and regularly. Individuals who have had a caesarean section often feel unable to perform daily activities. The research objective was to determine the effect of early mobilization on daily living activities based on dependence in postoperative caesarean section patients at the East Semar District General Hospital, Maluku. The research design used quasi-experimental methods The population was all patients with post-op section caesarea in the regional general hospital of east Seram regency. The sample was all patients with post-op section caesarea. The samples was taken by quota sampling. The data were collected by using a barthel instrument index, an early mobilization SOP, leaflets, and observation sheets and analyzed with marginal homogenity test. The results of the study proved that all respondents performed early mobilization, and most respondents experienced the activity daily living category independently in patients with post-operation cesarean sections. The results of the marginal homogeneity test obtained a p value of 0, which means that there was an effect of early mobilization on daily living activities based on dependence on postoperative caesarean section patients at the regional general hospital of East Seram Regency, Maluku. Based on the research results, it is necessary for further researchers to measure all the factors that affect the level of dependence on activity for daily living in the post-operation section caesarean